Understanding Dieting and Previous Weight Loss Attempts among Overweight and Obese Participants: Insights into My Body Is Fit and Fabulous at Work Program - Ismail, Tengku Alina Tengku; Jalil, Rohana Abdul; Ishak, Wan Rosli Wan; Hamid, Noor Fadzlina; Nik, Wan Suriati Wan; Mohamed, Hamid Jan Jan; Mohd, Nor Haslina; Arifin, Wan Nor; Mohamed, Wan Mohd Izani Wan; Ibrahim, Mohd Ismail; Ismail, Rohaida; Hassim, Tengku Fatimatul Tengku; et al. (Korean Academy of Family Medine, 2018)
Background A qualitative study providing an in-depth exploration of people's view and the increasing burden of overweight and obesity is required. This study aimed to explore the understanding of dieting and previous experiences on weight loss attempts among overweight and obese government employees in Kelantan, Malaysia, prior to recruitment into the intervention program.